O-019 Novel Method for Intracranial Deployment of 6 and 8 mm diameter Self Expanding Cobalt Chromium Stents in the Arterial and Venous Circulations. (29th July 2016) - Martin, C; Akhtar, I; Halpin, J; Holloway, W; Akhtar, N
Abstract : Introduction/purpose: Stents for the intracranial circulation are approved for stent assisted coiling of brain aneurysms, flow diversion of brain aneurysms and atherosclerotic occlusive disease. These stents are deliverable and approved for intracranial placement of cerebral arteries ranging in size from 2.5 to 4.5 mm. The relatively small stents are unsuitable for skull based internal carotid artery for dissection and venous sinus deployment due to the large diameter of these vessels. Self-expandable cobalt chromium carotid stents are properly sized to these circulations but do not track the curvatures of the intracranial arterial and venous circulations. These self-expanding cobalt chromium carotid stents are available in 6 and 8 mm diameter sizes and, due to the braided design, these implants will track curves when partially deployed. We report a technique of partially deploying a cobalt chromium stent within a 072 intracranial support catheter which has already been positioned distal to the target. This allows the stent to be advanced around curves and unsheathed directly from the catheter thus allowing intracranial stenting of larger vessels. Materials and methods: This is a retrospective review of 11 cases in which cobalt chromium stents were placed in the intracranial circulation at our facility over a two year period. These stents were placed with an 072 intracranial support catheter positioned distal to the target. Three stents were placed in distal cervical ICA transitioning into the horizontal petrous ICA. Eight stents were placed in the venous circulation (1 straight sinus to transverse sinus, 5 transverse sinus, 1 transverse-sigmoid junction, 1 sigmoid-jugular junction). In two venous cases, the stents were used to support coil masses. Results: All cases in which the cobalt chromium stents were deployed were successful. No neurological sequelae were observed post procedure. Conclusion: This technique allows for a wider range of stent sizes to access the tortuous intracranial circulation and provides an additional tool to the neurointerventional surgeon. Disclosures: C. Martin: None. I. Akhtar: None. J. Halpin: None. W. Holloway: None. N. Akhtar: None.